THE RELATIONSHIP BETWEEN TIKTOK USE INTENSITY AND SELF-COMPASSION AMONG ADOLESCENTS AT SMK BINTANG NUSANTARA KARANGANYAR - Aliya Nur Mawa Wulandari; Dyah Vierdiana; Nur Rakhmahwati (Journal of Advanced Nursing and Health Sciences, 2026)
Background: The development of technology and the internet has increased the variety of media people can use for communication, including social media. Social media applications, particularly TikTok, are most frequently used because they offer features that strongly align with the habits and interests of today’s adolescents. Self-compassion also helps adolescents avoid becoming trapped in feelings of low self-worth or negative social comparison; instead, it enables them to view each failure as a learning opportunity to grow into more mature and resilient individuals.Methods: This study employed a quantitative cross-sectional design. The study population comprised 282 female students in grades X and XI at SMK Bintang Nusantara Karanganyar. The sample in this study consisted of 74 students. This study applied Proportional Random Sampling as the sampling method. Data analysis was conducted using the Spearman Rank test. Results: The Spearman’s rank correlation test showed a very weak correlation (rho = 0.020) with no statistically significant relationship (p = 0.865) between TikTok use intensity and self-compassion among adolescents.Conclusion: The results of the study indicate that most students fall into the moderate category for TikTok usage. This indicates that TikTok is used fairly frequently in students’ daily lives, but usage is not yet at either a low or very high level.